Highly ordered of anatase titanium dioxide nanotube arrays at different calcination temperatures via electrochemical anodization method / Najwa Ezira Ahmed Azhar ... [et al.] - Ahmed Azhar, Najwa Ezira; Shuhaimi, Ahmad; Shariffudin, Shafinaz Sobihana; Rusop, Mohamad (Universiti Teknologi MARA Press (Penerbit UiTM), 2020)
Highly ordered titanium dioxide nanotube arrays (TNTAs) were fabricated via electrochemical anodization of Ti sheet in electrolyte containing aqueous and nonaqueous electrolyte. The formation of highly ordered TNTAs was varied by calcination temperatures (350, 450, 550oC) for 120 minutes to investigate the effect of calcination temperature on surface morphology, roughness, crystallinity and band gap energy. The field emission scanning electron microscopy revealed that the prepared TNTAs grow uniformly with average diameter in the range of 48.23 to 52.14 nm as the temperature increased from 350 to 550oC. The X-ray diffraction pattern showed the TNTAs exhibit anatase phase with prominent (101) peak recorded for the sample calcined at 450oC. The transformation from anatase to rutile phase appeared after calcination at 450oC. The band gap value (~3.24 eV) was obtained for all calcination temperature sample due to homogeneity of the TNTAs structures.